The association between level of personality organization and problematic gaming: Anxiety, depression, and motivations for playing as mediators. (September 2022) - Sibilla, Federica; Imperato, Chiara; Mancini, Tiziana; Musetti, Alessandro
Highlights: Low personality organization and depressive symptoms are risk factors for PG. Socializing and achievement motivations for playing are risk factors for PG. Symptoms secondary to low personality organization play a critical role towards PG. Depressive symptoms favor PG by increasing achievement motivation. Anxiety symptoms protect against PG by reducing achievement motivation. Abstract: Problematic gaming is a topic of great clinical and social relevance, so it is particularly important to identify its protective and risk factors. Literature already showed that maladaptive personality favors problematic gaming. In the light of Kernberg's model of personality organization, the present cross-sectional study aimed to evaluate the mediational process through which low level of personality organization associates with problematic gaming, exploring the role of depressive and anxious symptoms and of motivations for playing. A sample of 1036 video gamers filled in an online survey regarding: level of personality organization; depressive and anxious symptoms; socializing, achievement, and immersion motivations for playing; problematic gaming. The path analysis showed that lower level of personality organization associated with greater problematic gaming and that depressive (but not anxious) symptoms, and socializing and achievement (but not immersion) motivations positively mediated this relationship. Furthermore, results showed that psychopathological symptoms and achievement motivations sequentially mediated the relationship between low level of personality organization and problematic gaming, highlighting that depressive symptoms secondary to a low level of personality organization could lead to a risky use of video games, i.e., they could push to use video games to self-enhance oneself, a dysfunctional strategy that exposes to problematic gaming. The study gives some indications on the variables that associate with problematic gaming and has some practical relevance, providing suggestions in the design of effective problematic gaming prevention and treatment interventions.